Almost “Direct Route”: Ideological Meanings in the Construction of the Factory Identity of Uralmashplant Workers - L. V. Enina; N. B. Gramatchikova (Научный диалог)
The article is devoted to the study of factory identity based on the material of autobiographical texts of Uralmash workers written in 1967—1984. The novelty of the research is in the theoretical approach to identity as a discursive concept, which is structured by systematically recurring themes in personal narratives. The main focus is on ideological meanings in autobiographical texts. Their ritual and integrative functions are established, which are realized in the analyzed texts. The leading role of ideological meanings in describing the construction of a plant and in constructing the image of the enemy and the threat posed by it for the plant and the collective is shown. The ways to include memoirs of the theme of victims of political violence in the 1930s in the texts and to restore their names in the factory biography are discussed in the article. It is proved that the introduction of the theme of victims of political repression, as well as ritual formulas of ideological loyalty, reproduced by naive authors with involuntary distortions and deviations from the norms of written literary speech, results, among other things, in “corrosion” of the Soviet official discourse and is one of the factors that led to the “performative shift” characteristic of the late Soviet era. The analyzed text material has not previously been the object of research.